ผลของการออกกำลังกายแบบแอโรบิคกับเก้าอี้ต่อความเหนื่อยล้าและ ความสามารถในการทำหน้าที่ของร่างกายในผู้ที่เป็นโรคไตเรื้อรังที่ได้รับ การฟอกเลือดด้วยเครื่องไตเทียม - ธัญญารัตน์ บุญโทย (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2018)
Fatigue and a decreased functional capacity among persons with chronic kidney disease receiving hemodialysis are the most common problems. Exercise can relieve such problems. Chair aerobic exercise may be beneficial to this population. This quasi-experimental research study aimed to examine effects of chair aerobic exercise on fatigue and functional capacity among persons with chronic kidney disease receiving hemodialysis. Subjects were persons with chronic kidney disease receiving hemodialysis at Kawila Hospital and Theppanya Hospital, Chiang Mai, Thailand from December, 2013 to April, 2014. Thirty-four subjects were purposively selected and assigned into the control or experimental groupbased on their hemodialysis schedule, with 17 participants in each group. Subjects in the control group received routine care whereas, those in the experimental group participated in chair aerobic exercise for 12 weeks. Research instruments consisted of: 1) the chair aerobic exercise DVD and handbook, 2) the demographic data recording form, 3) Borg’s scale record form, 4) the Revised Piper Fatigue Scale (Piper et al., 1998) adapted and translated by Pritsanapanurungsie (2000), and 5) the 6 minute walk test record form. The data were analyzed using descriptive statisticsand t-test.